Bentuk Ketaatan Syekh Abdul Karim Pada Sang Guru Syekh Kholil Dalam Nadzom Al Mujtana : Kajian Psikologi Sastra - Darajati, Aflaha Putri (Maliki Interdisciplinary Journal, 2024)
Literary psychology study on a strand of poetry in the book Nadzom Al Mujtana written by Muis Muhsin. In a poem he tells the story of the greatness of a student’s obedience to the teacher, which is reflected by Sheikh Abdul Karim in Sheikh Kholil. So, by knowing Sigmund Freud’s psychological analysis, we can reveal the secret behind Sheikh Abdul Karim’s success in building a very famous Islamic boarding school, namely Lirboyo. This research is descriptive qualitative research on one of the selected poems. By classifying events exposed to syi’ir according to 3 basic personality systems, namely, id, ego and superego, we are able to reveal the model of a true seeker of knowledge, namely by feeling humiliated in front of his teacher who has privileges and as a role model for the student so that he can lead Sheikh Abdul Karim was a great and prominent person like Sheikh Kholil Al Bangkaani, his teacher.